Assessment of the maternal self-efficacy for child diarrhea prevention - Taís Capistrano Lopes; Anne Fayma Lopes Chaves; Emanuella Silva Joventino; Rebeca Silveira Rocha; Ana Rita Pimentel Castelo; Mônica Oliveira Batista Oriá (Universidade Federal do Ceará, 2014)
This study aims at assessing self-efficacy for preventing child diarrhea among mothers of children living in Quixadá, Ceará, Brazil. A descriptive, quantitative study was conducted in three Basic Health Units of Quixadá, CE, Brazil from March to May2012.We interviewed 150 mothers of children under five years, using the socio demographic form and the Maternal Self-Efficacy Scale for Child Diarrhea Prevention. 51.3% of children had had diarrhea, 89% of the mothers had low self-efficacy for preventing child diarrhea. Items that showed greater disagreement were "I am able to avoid my son putting dirty objects in his mouth" (10.2%), 'I am able to wash fruits and vegetables with sodium hypochlorite or bleach" (25.3%)and "I am able not to give my child left over meals' (25.3%). The majority (89.0%) of the mothers had low self-efficacy for preventing child diarrhea. Thus, maternal self-efficacy should be considered for the prevention of child diarrhea.